The effect of practice in mind (PIM) training on jumping performance of high jumpers - Azizan, A.; Ismail, M. (International Journal of Sports Science, 2018)
Imagery is defined as an experience that are created or recreated within the mind by using different sensory modalities such as kinesthetic, visual and auditory imagery which play an important role in Psychological Skills Training. Consequently, Practice in Mind (PIM) training is an appropriate combination of skill practices and imagery training technique program design in order to achieve the desired training goals. Therefore, this study attempted to investigate the effect of PIM training on jumping performance of high jumpers. A double-blind experimental design research was conducted to twenty-six high jumpers (n =26) aged between 13 to 17 years old. Participants were randomly assigned into two different groups (PIM group and control group) with 13 participants for each group. Both groups completed 18 training sessions three times per week in a six-week intervention program. The results showed that PIM group had significantly performed better in jumping performance compared to control groups. The finding supports the idea of using PIM training to improve sports skills performance. Additionally, high jumpers should not focus on their skills training only to be successful but also develop their psychology training particularly in imagery training.